Past climate changes, population dynamics and the origin of Bison in Europe. Issue 1 (December 2016) - Massilani, Diyendo; Guimaraes, Silvia; Brugal, Jean-Philip; Bennett, E.; Tokarska, Malgorzata; Arbogast, Rose-Marie; Baryshnikov, Gennady; Boeskorov, Gennady; Castel, Jean-Christophe; Davydov, Sergey; Madelaine, Stéphane; Putelat, Olivier; et al.
Abstract Background Climatic and environmental fluctuations as well as anthropogenic pressure have led to the extinction of much of Europe's megafauna. The European bison or wisent (Bison bonasus ), one of the last wild European large mammals, narrowly escaped extinction at the onset of the 20th century owing to hunting and habitat fragmentation. Little is known, however, about its origin, evolutionary history and population dynamics during the Pleistocene. Results Through ancient DNA analysis we show that the emblematic European bison has experienced several waves of population expansion, contraction, and extinction during the last 50, 000 years in Europe, culminating in a major reduction of genetic diversity during the Holocene. Fifty-seven complete and partial ancient mitogenomes from throughout Europe, the Caucasus, and Siberia reveal that three populations of wisent (Bison bonasus ) and steppe bison (B. priscus ) alternately occupied Western Europe, correlating with climate-induced environmental changes. The Late Pleistocene European steppe bison originated from northern Eurasia, whereas the modern wisent population emerged from a refuge in the southern Caucasus after the last glacial maximum. A population overlap during a transition period is reflected in ca. 36, 000-year-old paintings in the French Chauvet cave. Bayesian analyses of these complete ancient mitogenomes yielded new dates of the various branching events during the evolution ofBison and its radiation withBos, which lead us to propose that the genetic affiliation between the wisent and cattle mitogenomes result from incomplete lineage sorting rather than post-speciation gene flow. Conclusion The paleogenetic analysis of bison remains from the last 50, 000 years reveals the influence of climate changes on the dynamics of the various bison populations in Europe, only one of which survived into the Holocene, where it experienced severe reductions in its genetic diversity. The time depth and geographical scope of this study enables us to propose temperate Western Europe as a suitable biotope for the wisent compatible with its reintroduction.